(3OjhGf GdMGLQjs - (3MSGe GdOjf Hf YjSi Hf SfLQ Hf HgQGe Hf LHQjd GdEQHdj GdeYQha H` GdMGLQi,J (B639 (3g` s
(3ChdgG (B:s
(3bGd GdCejQ GdHGQY GdeYQha HGdMGLQj hcGfJ haGJg bGd GdeDda dgPG GdOjhGf (B((3GdLGeY dg(B) (3hgh SHjd GdhGba Ydi gPG GdOjhGf GdUaM YeG jLOg ef GdNWC hGdRdd s
(3BNQgG (B:s
(3OhHjJ(B: (3jG ef NWQGJg dbdHj ZeQJ gd JQL aj dYJGH Jdc GdfcJ bO bjd eMGSf GdUH dbjJ```````````gG jG XHj afi GdYeQ adG JdJaJ s
(3Vef eLehY , JQJjHgG (B: (3ef U (B36 - (3U(B65s
(3fSNI KGdKIs
(3bHd HOGjJgG JQLeI ddMGLQjs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B25s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B3 - (3U (B71 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B783s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdCOHs